(untitled) (Journal of Atomic and Molecular Sciences, 2021)
We have proposed a method to suppress simultaneously decoherence induced by spontaneous emission and thermal effect in a single two-level trapped ion system based on bang-bang scheme. The basic idea of this method is that two kinds of decoherences are both suppressed by using a series of large detuned pulses to drive the ion in a precision-designed manner, thus best results can be obtained with minimal resources.